Analytical hierarchy process application of body in white modular sub-assembly for automotive manufacturing in Malaysia - A case study - Fudzin, A.F. (2019)
Decision-making is crucial in the industry as the industrial expert having a restriction to convey their experience to the management prior to the final decision-making (DM). Daily operation in the industry especially in the automotive environment a lot of DM is required. Industry issue such as making decision of sub-assembly parts and module production location is one of the industry problem. The objectives of this study to establish a method to measure the intuitive opinions and experiences of the industrial expert for the DM proposal. Simple qualitative measurement would benefit to engineer to make a proposal to the management with the quantitative result. Intuition of the expert would conveyed to the decision maker in the industry to reach a decision on the proposal. Based on the criteria, sub-criteria and alternatives established, the computation using analytical hierarchy process (AHP) methodology applied in this study. The result of alternative 3 is 0.399, which is the processes will be outsource at the local component manufacturer location and transport to the automotive carmaker. The weighted factor in conclusion achieved the consistency with a CR â¤ 0.1, which is 0.07. Alternative 3 agreed by all related party in the industry as the best option for sub-assembly process of parts and modules in order to meet local contents strategy. The AHP methodology proven for usage as the appropriate tool for decision making in the industry. Â© Published under licence by IOP Publishing Ltd.